Components, design and effectiveness of digital physical rehabilitation interventions for older people: A systematic review - (:unkn) unknown (My University, 2020)
Background With the rapid advancement in digital technologies, the use of digital health applications is increasing day by day. Although a large number of digital applications have been developed for rehabilitation of older people, there has been no review of the evidence for effectiveness of these interventions. Methods The aim of our study was to review the evidence of digital rehabilitation interventions on outcomes including pain, function and quality of life in older people. We focused on digital interventions that are designed to improve and restore physical functioning. We searched six electronic bibliographic databases and included randomised controlled trials. Cochrane risk of bias tool and Cochrane’s Grading of Recommendations, Assessment, Development and Evaluation approach was used to evaluate the risk of bias and grade the evidence. Results Eight trials were included. The short-term effects of digital rehabilitation interventions on physical activity, quality of life, vertigo symptoms and falls are uncertain. Quality of trials was rated as very low to moderate evidence. Conclusion More research is needed to estimate effectiveness of these interventions.
Components, design and effectiveness of digital physical rehabilitation interventions for older people